Using peer tutoring to improve reading skills: a practical guide for teachers - Topping, K. Keith Topping; Duran,D. David Duran; Van Keer, H. Hilde Van Keer (London: Routledge, 2016)
Using Peer Tutoring to Improve Reading Skills is a very practical guide, offering a straightforward framework and easy-to-implement strategies to help teachers help pupils progress in reading. An introduction, it shows how schools can make positive use of differences between pupils and turn them into effective learning opportunities.
Includes bibliographical references and index.
Keywords: Reading -- Remedial teaching -- United States; Peer teaching; Tutors and tutoring